2017
DOI: 10.1136/jmedgenet-2017-104903
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, laboratory and molecular findings and long-term follow-up data in 96 French patients with PMM2-CDG (phosphomannomutase 2-congenital disorder of glycosylation) and review of the literature

Abstract: PMM2-CDG clinical phenotype is heterogeneous in terms of clinical course, with no clear division between neurological and visceral presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
116
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 48 publications
2
116
0
1
Order By: Relevance
“…Given that FIX, FXI, AT, PC, and PS are primarily affected in CDG, we chose to assay these coagulation factors. Indeed, we found that CDG syndrome affected the activity of clotting factors and plasma inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that FIX, FXI, AT, PC, and PS are primarily affected in CDG, we chose to assay these coagulation factors. Indeed, we found that CDG syndrome affected the activity of clotting factors and plasma inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent CDG is phosphomannomutase deficiency ( PMM2 ‐CDG) . The clinical symptoms of PMM2 ‐CDG may include failure to thrive, developmental delay, cerebellar ataxia, strabismus, skeletal findings, and cardiac or renal involvement . Coagulation factors, most of which are glycoproteins, are also frequently affected in CDG.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations